Neutrophils cast extracellular traps in response to protozoan parasites - Abdallah, Delbert S. Abi (Frontiers Media S.A., 2012)
Release of extracellular traps by neutrophils is a now well-established phenomenon that contributes to the innate response to extracellular bacterial and fungal pathogens. The importance of NETs during protozoan infection has been less explored, but recent findings suggest an emerging role for release of neutrophil-derived extracellular DNA in response to this class of microbial pathogens. The present review summarizes findings to date regarding elicitation of NETs by Toxoplasma gondii, Plasmodium falciparum, Eimeria bovis, and Leishmania spp.